A hemorrhagic transformation model of mechanical stroke therapy with acute hyperglycemia in mice. Issue 6 (7th January 2018) - Couret, David; Bourane, Steeve; Catan, Aurélie; Nativel, Brice; Planesse, Cynthia; Dorsemans, Anne‐Claire; Ait‐Arsa, Imade; Cournot, Maxime; Rondeau, Philippe; Patche, Jessica; Tran‐Dinh, Alexy; Lambert, Gilles; et al.
Abstract: Clinical benefit for mechanical thrombectomy (MT) in stroke was recently demonstrated in multiple large prospective studies. Acute hyperglycemia (HG) is an important risk factor of poor outcome in stroke patients, including those that underwent MT. The aim of this therapy is to achieve a complete reperfusion in a short time, given that reperfusion damage is dependent on the duration of ischemia. Here, we investigated the effects of acute HG in a mouse model of ischemic stroke induced by middle cerebral artery occlusion (MCAO). Hyperglycemic (intraperitoneal [ip] injection of glucose) and control (ip saline injection) 10‐week male C57BL6 mice were subjected to MCAO (30, 90, and 180 min) followed by reperfusion obtained by withdrawal of the monofilament. Infarct volume, hemorrhagic transformation (HT), neutrophil infiltration, and neurological scores were assessed at 24 hr by performing vital staining, ELISA immunofluorescence, and behavioral test, respectively. Glucose injection led to transient HG (blood glucose = 250–390 mg/dL) that significantly increased infarct volume, HT, and worsened neurological outcome. In addition, we report that HG promoted blood‐brain barrier disruption as shown by hemoglobin accumulation in the brain parenchyma and tended to increase neutrophil extravasation within the infarcted area. Acute HG increased neurovascular damage for all MCAO durations tested. HTs were observed as early as 90 min after ischemia under hyperglycemic conditions. This model mimics MT ischemia/reperfusion and allows the exploration of brain injury in hyperglycemic conditions. Abstract : The clinical benefit of mechanical thrombectomy in stroke was recently demonstrated in multiple large prospective studies. The aim of this therapy is to achieve a complete reperfusion in a short time. In a mouse model of middle cerebral artery occlusion, acute hyperglycemia increased infarct size, neurovascular damage, and hemorrhagic transformations. This model of ischemia/reperfusion allows the exploration of brain injury in hyperglycemic conditions.